Dos costumes da comédia à comédia de costumes : Martins Pena e o materialismo lacaniano - Paula, João Gabriel Pereira Nobre de (2016)
This dissertation aims to address to some plays of the Brazilian playwright Martins Pena, the precursor of comedy of manners in Brazil, using for this some concepts belonging to the Lacanian Materialism theory. Starting with a brief historical overview involving the question of laughter and of theatrical forms that established fundamental importance for the emergence of comedy of Martins Pena, this work finds its peak the consideration of violence in the play Os dous os o inglês maquinista and the tolerance in the play A família e a festa na roça, both concepts guided by i ek's perspective. Violence, when approached by the Lacanian materialism perspective, gains greater scope than only physical aggression, proposed by Slavoj i ek, subjective violence (being possible to recognize the perpetrators of violent acts). There are also aggregated elements within the sphere of objective violence, less noticeable, and it is divided into systemic and symbolic violence (the first rooted in our socio-historical concepts and the second present in the naturalization of a process, as the consideration of inferiority of a particular class or ethnicity, incorporating speech and thoughts). Whereas tolerance, far from being a passive acceptance of other show its most nefarious sphere when it admits only considering the other as an individual with values, beliefs and attitudes that are not diametrically opposed to them.